Proposta de um estudo sobre filosofia da educação espírita - Fanini, Tatyana Stefani (2017)
This present work enabled analyze the construction of the educational thinking in the figures of Augusto Comte and Allan Kardec, for the education. Besides being mentioned, the different philosophical views, the positive philosophy and the spiritualistic philosophy, it was possible to demonstrate the continuity of the Proposal of the Spiritualistic Philosophy Education, which from the analyzes of the spiritualistic philosophy of the productions of Allan Kardec, approached two pedagogical theories, the reason theory and the activity theory under emphasis of the spiritualistic and historic-cultural perspectives. It was realized that the spiritualistic philosophy, because of being an application philosophy, brings guiding principles to the spiritualistic pedagogy and its contribution for the teaching-learning process. The experience of the Spiritualistic Education which philosophical roots propose moral education and not just a technical formation, but a formation that available the man the full development of his capabilities, understanding that the evolution is complete in human being when he join willingness, feeling and his conscience awake in reason. Thinking of the formation (teacher/student), the spiritualistic education understands that the human being forms and is formed in experience, when taken by his awaken conscience he build possibilities of action to develop the faculties of the integral man. The spiritualistic educator forms the pupil strengthening his willingness and stimulating his thoughts.